(untitled) (Biological Sciences - PJSIR, 2004)
A hot aqueous decoction of the leaves of Euphorbia heterophylla Linn (Euphorbiaceae) 1.24 kg gave on cooling and defatting with dichloromethane, an aqueous solution which on successively extracting with n-butanol and ethylacetate gave 25.89g and 1.31g of residue, respectively on removal of solvent. The semi-solid extract from the ethylacetate frac- tion on hydrolysis with dilute tetraoxosulphate (VI) acid gave a yellow powder which on acetylation gave colourless needle clusters identified as quercetin tetracetate. The butanolic fraction had laxative action and contained saponins, phenols, terpenes and diterpenes identified as phorbols but no anthraquinones. The residual aqueous solution contained mainly sugars identified as xylose, maltose, galactose, lactose and lactulose, which are bulkforming laxatives. The purga- tive action was found to be a joint action of both the phorbols in the butanol fraction and the bulk forming laxative sugars in the residual aqueous fraction.